Gaseous and Solid Emissions from Combustion of a Bio-solid Waste in Fluidized - Vamvuka, D.; Alexandrakis, S. (Journal of Environmental Science and Engineering Technology, 2019)
The gaseous emissions and the combustion efficiency of a bio-solid waste from a wastewater treatment plant were determined, as a function of excess air ratio and reactor loading, by conducting combustion tests in a bubbling fluidized bed system. Fly and bottom ashes were subjected to mineralogical and chemical analyses. According to the results, the bio-waste studied burned with a uniform temperature along the fluid bed unit. CO, SO2 and NOx emissions were below allowable limits, except those of SO2 at excess air ratio λ=1.5 and those of NOx at excess air ratio λ=1.3. An increase of excess air from 30% to 50%, or a reduction of the feeding rate from 0.6 to 0.48kg/h resulted in lower SO2 and NOx emissions, whereas higher CO emissions. Under test conditions, combustion efficiencies ranged between 98.5 and 98.8%. An improved performance was achieved at a lower reactor loading and a higher excess air ratio. Fly ashes were enriched in Si and P minerals, as well as Cu, Zn and Sr trace metals. All trace element values fulfilled EU legislation for landfill disposal.